Taxpayer Compliance Determinants in Digital Tax Administration: Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak dalam Administrasi Pajak Digital - Indi Luthfiyati; Wiwit Hariyanto (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Taxpayer compliance is a fundamental component of sustainable public revenue systems. Specific Background The adoption of digital tax administration and behavioral factors has become increasingly relevant in improving compliance among MSME taxpayers. Knowledge Gap Limited empirical studies simultaneously examine taxation knowledge, electronic tax systems, sanctions, and risk preference within a single analytical framework. Aims This study aims to analyze the relationships between these factors and taxpayer compliance. Results The findings indicate that taxation understanding, electronic tax systems, and tax sanctions are statistically associated with compliance, with risk preference functioning as a moderating variable. Novelty This study provides contextual empirical evidence by integrating behavioral and technological variables within MSME taxpayer settings. Implications The results offer insights for tax authorities in designing compliance-oriented digital tax policies and taxpayer education strategies. Keywords: Taxpayer Compliance, Taxation Knowledge, Electronic Tax Systems, Tax Sanctions, Risk Preference Key Findings Highlights: Digital tax mechanisms are linked to compliance behavior Behavioral considerations shape taxpayer responses Risk orientation moderates compliance-related factors